First report of cleaning behaviour in white sea bream (Diplodus sargus) - Abecasis, D. (2017)
Several studies have reported the existence of ectoparasites in the stomach contents of Diplodus sargus. The cleaning behaviour has, however, never been previously observed for this species. In this short study, we report the first observations of the cleaning behaviour of D. sargus. These observations were in two yachting marinas, located in the Portuguese western coast between the months of April and August. The cleaning behaviour was only observed towards two Mugilidae species, Chelon labrosus and Mugil cephalus.